The environmental dependence of the stellar velocity dispresion of active galactic nucleus (AGN) host galaxies and dependence of the clustering properties of AGN host galaxies on the stellar velocity dispersion - Yong Xin; Xin-Fa Deng (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
We use two volume-limited active galactic nucleus (AGN) host galaxy samples constructed by Deng & Wen [47], and explore the environmental dependence of the stellar velocity dispersion in these two volume-limited AGN host galaxy samples. In the luminous volume-limited AGN host galaxy sample, the stellar velocity dispersion of AGN host galaxies apparently depends on local environments: AGN host galaxies with large stellar velocity dispersion exist preferentially in high density regime, while AGN host galaxies with small stellar velocity dispersion are located preferentially in low density regions. But in the faint volume-limited AGN host galaxy sample, this dependence is fairly weak. We also examine the dependence of the clustering properties of AGN host galaxies on the stellar velocity dispersion by cluster analysis, and find that in the luminous volume-limited AGN host galaxy sample, AGN host galaxies with small stellar velocity dispersion preferentially form isolated galaxies, close pairs and small groups, while AGN host galaxies with large stellar velocity dispersion preferentially inhabit the dense groups and clusters. In the faint volume-limited AGN host galaxy sample, although the fraction of isolated galaxies with small stellar velocity dispersion is apparently higher than the one with large stellar velocity dispersion, the trend in the luminous volume-limited sample is very difficultly observed. This likely is due to the galaxy number of the faint volume-limited AGN host galaxy sample being too small to ensure an ideal statistical analysis. Использованы две выборки родительских галактик с активными ядрами (АЯГ) с ограниченным объемом, построенные Денгом и Веном, и исследована зависимость дисперсии звездных скоростей от окружающей среды в этих двух выборках родительских галактик ограниченного объема. В выборке сравнительно ярких родительских галактик АЯГ с ограниченным объемом дисперсия звездных скоростей родительских галактик АЯГ, по- видимому, зависит от локального окружения: родительские галактики АЯГ с большой дисперсией звездных скоростей наблюдаются преимущественно в областях с высокой плотностью, в то время как родительские галактики АЯГ с малой дисперсией звездных скоростей - с низкой плотностью населения. Но в выборке слабых родительских галактик АЯГ, ограниченных по объему, эта зависимость довольно слабая. Изучена также зависимость свойств кластеризации родительских галактик АЯГ от дисперсии звездных скоростей с помощью кластерного анализа и обнаруженo, что в выборке ярких родительских галактик АЯГ с ограниченным объемом родительские галактики АЯГ с малой дисперсией звездных скоростей предпочтительно образуют изолированные галактики, близкие пары и небольшие группы, в то время как галактики с большой дисперсией звездных скоростей преимущественно населяют плотные группы и скопления. Несмотря на то, что в выборке слабых галактик, ограниченных по объему, доля изолированных галактик с малой дисперсией звездных скоростей, по-видимому, выше, чем с большой, тренд наблюдается с трудом. Вероятно, это связано с тем, что число галактик в выборке слабых галактик с ограниченным объемом слишком мало для обеспечения идеального статистического анализа.
Keywords: Astrophysics